Plethora of Traumatic Lesions of Bilateral Knee Extensor Mechanism in Osteogenesis Imperfecta - Kloen, Peter; Hamdy, Reggie Charles; Bech, Niels Hendrik (Frontiers in Endocrinology, 2021)
Introduction Injuries to the quadriceps extensor mechanism are rare in patients with Osteogenesis Imperfecta (OI). To the best of our knowledge, non-union of the patella in OI, either as an isolated problem or in combination with an acute fracture, has not been previously reported. Case report We describe how we surgically approached both the fracture and the non-union simultaneously. The surgical technique and steps are described in detail. Post-operative course was uneventful and the outcome was favorable, with full return of function for the patient. Conclusion A review of various knee extensor mechanism injuries in OI is described as illustrated in a single patient. The unusual simultaneous surgical treatment of a non-union and an acute fracture in the same patella shows that despite the severely compromised bone in this rare bone disease the bone still has a capacity to heal with a functional outcome.